Herpes Zoster pada Pasien Dewasa Muda : Laporan Kasus - Andra Nabila Fauziani; Winda Trijayanthi Utama (CV. Jasa Sukses Abadi, 2026)
Herpes zoster is a reactivation of latent Varicella-zoster virus (VZV) infection that commonly occurs in older adults and immunocompromised individuals, but it may also develop in immunocompetent young adults. This case report aims to describe the clinical manifestation, diagnosis, and management of maxillary branch trigeminal herpes zoster in a young patient without known major risk factors. A 20-year-old woman presented to the Dermatology and Venereology Outpatient Clinic of Dr. H. Abdul Moeloek Hospital with painful vesicular eruptions accompanied by a burning sensation on the left cheek that had appeared four days before presentation. Dermatological examination revealed grouped vesicles on an erythematous base distributed unilaterally along the maxillary branch of the trigeminal nerve without crossing the midline. The diagnosis was established based on history taking and characteristic clinical findings without laboratory confirmation. The patient was treated with oral acyclovir, gabapentin, and supportive therapy. Follow-up evaluation two days after treatment showed no new lesions, gradual crusting of vesicles, and improvement of pain and burning sensation. This case demonstrates that herpes zoster may occur in immunocompetent young adults without identifiable predisposing factors and should therefore remain a differential diagnosis of unilateral vesicular facial eruptions. Accurate clinical diagnosis and timely antiviral therapy are important to promote clinical improvement and prevent complications.